We are now omnidextrous to sustain! Story of CERA India - Dipak Kumar Bhattacharyya (Vilakshan (XIMB Journal of Management))
Purpose – This study aims to help students to relate their theoretical knowledge in managing change in a crisis. It is more relevant in today’s pandemic situation and could be a morale booster for many entrepreneurs who are struggling to sustain. Design/methodology/approach – It is based on managing real-life change situation in organization, and it is presented in narrative form. Findings – CERA India could successfully transform and sustain in Covid-19 pandemic situation with an inclusive approach, without losing their identity. Research limitations/implications – This study is based on consulting experience and success story of one organization in pandemic situation. Important message is in a crisis, organizations can sustain partnering with people. But, this depends on the prevalent culture of the organization. Also, other organizations before replication need to ascertain the problem of their brand dilution, for shifting their focus to other product lines. Practical implications – This story can be used in organizational change management classes, and students may be assigned to document their lessons. At the end of the story, some possible areas of investigation for students are listed for getting appropriate direction. Social implications – In this pandemic situation, this study is socially relevant, as it shows how organizations can sustain with a human face. Originality/value – This study is original and based on real-life experience in managing organizational transformation in a crisis situation. The name of the organization is imaginary, as organization did not like their name in public. This is one reason of not using their data for tabular presentation.